Vegetation Analysis on the Upper Mahakam River Border - Suparjo; Herijanto Thamrin; Sri Jimy Kustini; F. V. Astrolabe Sian Prasetya; Rukmi; Iswinanto Denis (Poltanesa, 2023)
Vegetation analysis on the upper Mahakam river border. The Mahakam River Basin (DAS) is very wide, reaching 7.724.300 Ha. The condition of the vegetation in the Mahakam watershed continues to change due to the development of plantations, mining, and settlements. On the other hand, efforts to maintain biological resources from the diversity of vegetation are needed to protect against extinction. Remote sensing data can be used to differentiate between primary and secondary vegetation economically. However, it has limitations for detecting vegetation composition and the number of individuals per unit area. Therefore, field surveys in the context of conducting vegetation analysis are still needed to complement remote sensing data. This study aims to analyze the vegetation in each growth phase, namely the seedling, sapling, pole, and tree phases on the Mahakam riverbank. The method used is to make observation plots of 13 plots for each growth phase. Plots of 2 x 2 m2 for seedling observation, 5 x 5 m2 for sapling level, 10 x 10 m2 for pole level, and 20 x 20 m2 for tree level observation. Based on data analysis, the seedling stage consisted of 30 species, the average number of stems was 25576.9 per ha, the species diversity index was 1.371, and the highest important value index was 21.8% of Coffea robusta. There were 17 species of saplings, an average number of 4,092.3 stems per hectare, a diversity index of 1,118, and the highest important value index of 39.5% from Theobroma cacao. The pole level contained 16 species, the average number of stems was 1023.1 per hectare, the diversity index was 1.138, and the highest interest index was 23.7% for Paraserianthes falcataria. The tree level consists of 30 species. The average number of stems is 255.8 per hectare, the diversity index is 1.282, and the highest important value index is 54.9% of Durio zibethinus. From the results of the study, it can be concluded that most of the vegetation in the Mahakam riverbank area is former fields or agricultural activities.